Zinc Oxide Nanoparticle Caused Plasma Metabolomic Perturbations Correlate with Hepatic Steatosis - Zhang, Weidong; Zhao, Yong; Li, Fuli; Li, Lan; Feng, Yanni; Min, Lingjiang; Ma, Dongxue; Yu, Shuai; Liu, Jing; Zhang, Hongfu; Shi, Tianhong; Li, Fuwei; et al. (Frontiers in Pharmacology, 2018)
Zinc oxide nanoparticles (ZnO NPs), known for their chemical stability and strong adsorption, are used in everyday items such as cosmetics, sunscreens, and prophylactic drugs. However, they have also been found to adversely affect organisms; previously we found that ZnO NPs disrupt pubertal ovarian development, inhibit embryonic development by upsetting -H2AX and NF-B pathways, and even disturb skin stem cells. Non-targeted metabolomic analysis of biological organisms has been suggested as an unbiased tool for the investigation of perturbations in response to nanoparticles and their underlying mechanisms. Although metabolomics has been used in nanotoxicological studies, very few reports have used it to investigate the effects of ZnO NPs exposure. In the current investigation, through a metabolomics-based approach, we discovered that ZnO nanoparticles caused changes in plasma metabolites involved in anti-oxidative mechanisms, energy metabolism, and lipid metabolism in hen livers. These results are in line with earlier findings that ZnO NPs perturb the TCA cycle and in turn result in the use of alternative energy sources. We also found that ZnO NPs disturbed lipid metabolism in the liver and consequently impacted blood lipid balance. Changes in plasma metabolomes were correlated with hepatic steatosis. Therefore, such metabolites might be used as potential biomarkers to evaluate the metabolic toxicity of ZnO NP exposure.